English english: english - Artarina DA Samoedra; Theresia Marditama; Ridono Caesar Suhud; Harun H. Trismiyanto; Nadya Hasna; Hennisa Salma; Sheila Azzahra (International Journal Of Humanities Education and Social Sciences (IJHESS), 2026)
This study examines the synergistic effects of health center service quality and patient knowledge on patient satisfaction at a community health center (Puskesmas) in Cimahi City, West Java, Indonesia. A quantitative methods was employed with data collected from purposively selected adult respondents residing in the Cimahi Tengah Sub-district who had utilized Puskesmas services within the preceding six months. Service quality was operationalized using the SERVQUAL instrument covering five dimensions: reliability, responsiveness, assurance, empathy, and tangibles. Patient knowledge and patient satisfaction were each measured using validated instruments adapted from established references. All instruments demonstrated satisfactory internal consistency. Path analysis using LISREL software was employed to assess direct and causal relationships among variables. Results indicated that service quality exerted a significant direct positive effect on patient satisfaction, as did patient knowledge. Simultaneously, both variables jointly explained a substantial proportion of the variance in patient satisfaction, confirming the synergistic contribution of the two predictors. These findings underscore the importance of a dual strategy combining continuous service delivery improvement and systematic patient health-literacy programs to achieve higher patient satisfaction in Indonesian primary healthcare settings